Hepatotoksik terkait Obat Antituberkulosis pada Pasien Tuberkulosis dan Koinfeksi Tuberkulosis-HIV - Azmi, Rizki Nur; Ardiani, Tiara; Siami, Sahra (RSUP Dr. Kariadi, 2022)
BACKGROUND : The side effect of antituberculosis drugs that is toxic to liver cells, called hepatotoxic, needs to be a concern in the treatment of tuberculosis. The presence of these unwanted side effects poses a challenge in treatment because it can lead to discontinuation oh therapy or a change in regimen. Coinfection with HIV is also thought to increase the potential for hepatotoxicity of antituberculosis drugs. OBJECTIVE: This study aims to determine the incidence of hepatotoxicity of antituberculosis drugs in patients with tuberculosis and tuberculosis-HIV coinfection. METHOD : This study is an observational study with a cross sectional design, which was conducted in one of the hospitals in Samarinda City. Sources of research data came from patient medical record in 2018 – 2020. There was 53 tuberculosis patients and 53 tuberculosis-HIV coinfection patients. Differences in live enzyme values (AST and ALT) and severity in the two groups were analyzed by Mann-Whitney and Chi-Square tests. RESULT : The average value of AST and ALT in tuberculosis-HIV coinfection patients were higher than patients without HIV infection, which is AST 127,1 µ/L and ALT 100,7 µ/L. The highest degree of severity experienced by the patient was grade 3 (severe hepatotoxicity). Tuberculosis-HIV coinfection patients with grade 3 severity were 22,6% and tuberculosis patients were 9,4%. The values of liver enzymes and the severity of hepatotoxicity in the two groups of patients were statistically significant with p value < 0,05. CONCLUSION : Tuberculosis-HIV coinfection patients tend to have a higher incidence of hepatotoxicity related to antituberculosis drugs than those without HIV infection.